Physiotherapy in ankylosing spondylitis - Balcerska, Kamila; Bielejewska, Marta; Gąsior, Paulina; Wrzesiński, Bartłomiej (Journal of Education, Health and Sport, 2018)
Ankylosing spondylitis (AS) is a chronic and progressive systemic disease characterized by the occurrence of inflammation and later ossification in the sacroiliac joints, spine joints, peripheral joints and tendons. It causes pain, swelling, limitation of mobility and partial or complete stiffness of the spine joints. AS is the second most common inflammatory disease of the joints right after rheumatoid arthritis. In most patients, the first symptoms appear between 15 and 40 years of life. In 90% of patients, the presence of HLA-B27 antigen is found. However, not everyone with this antigen will be affected by AS. This disease is 2-3 times more likely to affect men than women.